âEFâ Method to Determine Books Inventory Number on Book Acquisition at Library of Lampung Unversity case study : acquisition book at 2012 and 2013 - Fitriani, Erni (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
Inventory is an activity of book registration or recording bibliographic data collection into the main book or book inventory in accordance with the type of collection. Before September 2012, the inventory of books, especially in determining books inventory number, have been done by manual counting, so it often goes wrong in the book inventory. In November 2012 at the Library of Lampung University, Acquisition Book Division received 1473 titles/7357 copies. In 2013, the Library have received 1684 titles/16.870 copies. The books that received from the publishers was composed in a box in random order. The aims of âEFâ method are: 1) to determine books inventory number easier, more effective, and faster; 2) to minimize the error in determining books inventory number. The method used is descriptive quantitative which consists of making a description, an image or picture in a systematic and factual from the existing problems which is to determine the books inventory number: a case study in acquisition books in 2012 and 2013Â The results and conclusion are âEFâ method in determining the books inventory number in 2012 and 2013 is easier, more effective, and faster, and âEFâ method can minimize errors in determining the books inventory number.Â